Investigating the role of religiosity as a deterrent against digital piracy - Casidy, R.; Lwin, Michael; Phau, Ian (Emerald Group Publishing Limited, 2017)
© 2017, © Emerald Publishing Limited.Purpose: The purpose of this paper is to examine the role of religiosity as a deterrent to habitual digital piracy behaviour. Specifically, it will examine the extent to which “religious teaching” affects consumer attitudes towards digital piracy and their habitual digital piracy behaviour in a developing market. Design/methodology/approach: In total, 400 usable samples were collected from large religious organisations in Indonesia using convenience sampling. The latent moderation structural equation technique was used to test the research hypotheses. Findings: The results indicated that: facilitating conditions are a significant driver of digital piracy habit; attitude towards piracy is a significant deterrent of digital piracy and moderates the relationship between facilitating conditions and habitual digital piracy; and religious teaching is a significant deterrent of digital piracy habit, mediated by attitude towards piracy. Originality/value: This study investigates the influence of Christian religious teaching as a deterrent to digital piracy behaviour. Further, it investigates the mediating and moderating role of attitude in a digital piracy context. The study findings would provide insights for policy makers to deter digital piracy behaviour through the use of religious appeals.